2019
DOI: 10.1111/jvim.15598
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of noninvasive shear wave elastography for the assessment of hepatic fibrosis in dogs with hepatic disease

Abstract: Background Two‐dimensional shear wave elastography (2D‐SWE) can noninvasively evaluate hepatic elastic modulus as shear wave velocity (SWV). Additionally, it may predict the presence of clinical relevant hepatic fibrosis (≥F2) in dogs with hepatic disease. Objectives To investigate whether SWV measured by 2D‐SWE can differentiate between dogs with (≥F2) and without (F0‐1) clinically relevant hepatic fibrosis. Animals Twenty‐eight client‐owned dogs with hepatic disease and 8 normal healthy Beagle dogs were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 35 publications
(85 reference statements)
3
45
2
Order By: Relevance
“…There is no values of liver and spleen stiffness of brachycephalic dogs described, which challenges our data comparison. However, a recent study evaluating liver fibrosis in dogs by shear wave elastography showed that dogs without clinical relevant fibrosis had a median SWV of 1.56 m/s whilst dogs with clinically relevant fibrosis had a median SWV of 2.04 m/s 36 . Although the dogs in the first group were classified without clinically significant liver fibrosis, some were histopathological affected and had similar SWV values to the observed in our brachycephalic dogs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…There is no values of liver and spleen stiffness of brachycephalic dogs described, which challenges our data comparison. However, a recent study evaluating liver fibrosis in dogs by shear wave elastography showed that dogs without clinical relevant fibrosis had a median SWV of 1.56 m/s whilst dogs with clinically relevant fibrosis had a median SWV of 2.04 m/s 36 . Although the dogs in the first group were classified without clinically significant liver fibrosis, some were histopathological affected and had similar SWV values to the observed in our brachycephalic dogs.…”
Section: Discussionmentioning
confidence: 97%
“…The SWV obtained by elastographic studies depends on the tissue stiffness being highly shaped by fibrosis and has a good predictive value for its presence 22 . Thus, the liver SWV increases along the histopathological grades of liver fibrosis in children and adults [40][41][42] as well as in dogs 35,36 . There is no values of liver and spleen stiffness of brachycephalic dogs described, which challenges our data comparison.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In veterinary literature, 2D SWE was applied to distinguish malignant from benign conditions of mammary tumors and lymph nodes and to evaluate the margination and acute changes in stiffness of the ablated liver tissue after radiofrequency ablation in dogs (Glińska-Suchocka et al, 2013;Feliciano et al, 2017;Lee et al, 2018;Silva et al, 2018). Recently, 2D SWE confirmed that the SWS in dogs with clinically relevant hepatic fibrosis was significantly higher compared to those in healthy dogs and dogs without clinically relevant hepatic fibrosis (Tamura et al, 2019b). In addition, 2D SWE revealed the different SWS in dogs with suspected pancreatic diseases and clinically healthy dogs (Avante et al, 2020).…”
Section: Introductionmentioning
confidence: 99%